Happy bonsai : choose it, shape it, love it - Tran, Michael (DK, 2020)
Anyone can become a bonsai artist. This book will show you how, through care profiles for 40 top trees and illustrated demonstrations of more than 20 bonsai techniques and styles. Select the right tree, learn how to keep it thriving, and shape your bonsai into a beautiful living sculpture. Do you know what a "nebari" is? Can you tell a raft display from a forest group? When is the right time to prune? How do you create a windswept look? Happy Bonsai has all the answers. Each tree profile provides easy-to-follow growing information, with day-to-day and seasonal care advice, along with ideas and tips for how to shape. Specialist techniques - such as repotting, wire training, defoliating, and root and branch pruning - are explained with illustrations. Techniques are then put into practice with demonstrations of how to achieve the main bonsai styles, from an informal upright tree to a forest group or root-over-rock. Making bonsai accessible to everyone, Happy Bonsai will help you fall in love with this meditative garden craft.